Characterization of bioactive compounds in fenugreek genotypes in varying environments: diosgenin, trigonelline, and 4-hydroxyisoleucine - Coban, Furkan; Ozer, Hakan; Yilmaz, Bilal; Lan, Yuzhou (Frontiers in Plant Science, 2025)
This study investigates the effects of irrigated and non-irrigated conditions on the bioactive compound content in fenugreek (Trigonella foenum-graecum) across 31 diverse genotypes from various geographical regions. The study was conducted at Atatürk University Research and Extension Center, Türkiye (N 39°55’59.9”, E 41°14’10.6”, altitude 1789 m) during the 2021 and 2022 growing seasons. The levels of diosgenin, trigonelline, and 4-hydroxyisoleucine analyzed under irrigated and non-irrigated conditions were found to be significantly influenced by genotype, environment, and their interaction (Genotype × Environment), with a highly significant effect observed at the p < 0.001 level. The compounds analyzed included diosgenin (0.50-0.93%), trigonelline (5.22-13.65 mg g-¹), and 4-hydroxyisoleucine (0.41-1.90%). Notably, genotypes such as Sivas/TR, Amasya/TR, Konya/TR and Samsun/TR exhibited higher diosgenin content across all conditions, while Spain, Malaysia, France, and India showed higher trigonelline content under irrigation. Variability in 4-hydroxyisoleucine content was observed, with some genotypes showing stability across different environmental conditions. A negative correlation between diosgenin and trigonelline was observed in fenugreek. Furthermore, Principal Component Analysis (PCA) and cluster analysis were found to be effective in revealing genetic diversity, morphological differences, and genotype adaptability. The findings highlight the potential for selecting superior genotypes for breeding programs focused on enhancing bioactive compound yields, especially under varying irrigation and non-irrigated conditions. This research emphasizes the critical role of environmental and genetic factors in optimizing the production of health-benefiting compounds in fenugreek.